2019
DOI: 10.1002/cam4.2037
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective efficacy analysis of immune checkpoint inhibitors in patients with EGFR‐mutated non‐small cell lung cancer

Abstract: Background Treatment with epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs) leads to initial response in most patients with EGFR‐mutated non‐small cell lung cancer (NSCLC). In contrast, little is known of the subpopulation of patients with NSCLC with EGFR mutations who exhibit clinical outcomes that require treatment with immune checkpoint inhibitors (ICIs). Therefore, to identify eligible cases to treat with ICIs, we retrospectively analyzed the correlation between clinical features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 31 publications
7
82
1
Order By: Relevance
“…Additionally, T790 M(−) patients had significantly lower FOXP3+ TILs than did T790 M(+) patients (P = 0.013). Furthermore, in a retrospective study by Yamada et al [118] including 27 patients with EGFR-TKI resistance who were treated with ICIs, subgroup findings supported that T790 M(−) patients were more likely to derive greater benefit from PD-1 inhibitor treatment (median PFS: 86 days vs 48 days, P = 0.03; median TTP: 97 days vs 48 days, P = 0.03) than were T790 M(+) patients. In the study of 67 EGFR-mutant NSCLC patients, the prevalence of PD-L1 expression was significantly lower in T790 M(+) tumors than in T790 M(−) tumors (P = 0.0149), and better survival was associated with PD-L1(−) / T790 M(+) tumors [152].…”
Section: T790 M Mutation Status and The Effectiveness Of Immune Checkmentioning
confidence: 89%
See 3 more Smart Citations
“…Additionally, T790 M(−) patients had significantly lower FOXP3+ TILs than did T790 M(+) patients (P = 0.013). Furthermore, in a retrospective study by Yamada et al [118] including 27 patients with EGFR-TKI resistance who were treated with ICIs, subgroup findings supported that T790 M(−) patients were more likely to derive greater benefit from PD-1 inhibitor treatment (median PFS: 86 days vs 48 days, P = 0.03; median TTP: 97 days vs 48 days, P = 0.03) than were T790 M(+) patients. In the study of 67 EGFR-mutant NSCLC patients, the prevalence of PD-L1 expression was significantly lower in T790 M(+) tumors than in T790 M(−) tumors (P = 0.0149), and better survival was associated with PD-L1(−) / T790 M(+) tumors [152].…”
Section: T790 M Mutation Status and The Effectiveness Of Immune Checkmentioning
confidence: 89%
“…The G719X mutation in exon 18 (3%) [113] and the L861X mutation in exon 21 (2%) [114] are the most common uncommon mutation types; G719X, L861X, and additional mutations in exon 20 and exon 19 are also considered favorable for effective EGFR-TKI treatment [115][116][117]. Recently, multiple studies have shown that NSCLC patients with uncommon EGFR mutations are more likely to benefit from immunotherapy than are those with common EGFR mutations [118,119].…”
Section: Cell Surface Molecules and Selected Soluble Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, immunotherapy represented by immune-checkpoint inhibitors (ICIs) have impressively achieved success and anti-programmed cell death-1 (PD-1)/anti-programmed cell death ligand-1 (PD-L1) inhibitors have been approved by the United States Food and Drug Administration (FDA) for the treatment of advanced NSCLC. However, EGFR-mutant NSCLC patients rarely derive a signi cant bene t from ICIs therapy [7][8].…”
Section: Introductionmentioning
confidence: 99%